ADVERSITY QUOTIENT DAN KOMITMEN ORGANISASI FUNGSIONARIS LKF FAKULTAS PSIKOLOGI UNIVERSITAS KRISTEN SATYA WACANA (UKSW) - Bernike Rosalia Rahayu; Sutarto Wijono (Bajang Institute, 2025)
This research is motivated by the importance of organizational commitment in increasing productivity and loyalty to the organization and as a basis for each member to continue to actively participate in efforts to achieve organizational goals. One factor suspected of being related to organizational commitment is the adversity quotient. This study aims to determine the relationship between the adversity quotient and organizational commitment among LKF functionaries at the Faculty of Psychology, UKSW. The research method used is quantitative with a correlational approach. The research sample consisted of 88 functionaries taken using a total sampling technique. The instruments used included the Adversity Response Profile (ARP) by Stoltz & the Organizational Commitment Questionnaire (OCQ) by Allen and Meyer. Data analysis was carried out using the Pearson correlation test with the help of the Jamovi program. The results of the study showed a positive and significant relationship between the adversity quotient and organizational commitment (r = 0.788; p < 0.05). Thus, it can be concluded that the higher the adversity quotient, the higher the level of organizational commitment. This finding implies the importance of a participatory adversity quotient in increasing organizational commitment